Jesus, history, and Mount Darwin an academic excursion - Kennedy, Rick. (Cambridge : Lutterworth Press, 2008)
Written in the genre of Henry David Thoreau's travel-thinking essays, Jesus, History, and Mount Darwin: An Academic Excursion is the story of a three-day climb into the Evolution Range of the High Sierra mountains of California. Mount Darwin stands among other near-14,000-foot high mountains that are named after promoters of religious versions of evolutionary thinking. Rick Kennedy, a history professor from a small college, uses the climb as an opportunity to think about general education and how both the natural history of evolution and the ancient history of Jesus can find a home in the Aris.
Front cover ; Title page; Copyright; Dedication; Contents; 1. The Plan ; 2. Road Trip ; 3. Base Camp ; 4. Mount Darwin ; 5. Homeward ; Afterword; Bibliography; Back cover.
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: Jesus Christ; Jesus Christ; Jesus Christ; Natural history; History, Ancient; RELIGION -- Philosophy; History, Ancient; Natural history; RELIGION / Philosophy; Electronic books